Rhes depletion promotes striatal accumulation and aggregation of mutant huntingtin in a presymptomatic HD mouse model - Pan, Yongcheng; Tang, Beisha; Li, Xiao-Jiang; Li, Shihua; Liu, Qiong (Frontiers in Aging Neuroscience, 2023)
Huntington's disease (HD) is a neurodegenerative disorder caused by the expansion of CAG trinucleotide repeats in the Huntingtin (HTT) gene. Increasing evidence suggests that Rhes (Ras homolog enriched in striatum) may play a critical role in the selective striatal degeneration in HD, however, it remains controversial whether Rhes acts as a protective or detrimental factor. Here, we investigate the effects of Rhes knockdown via CRISPR/Cas9 at different disease stages in HD knock-in (KI) mice. We found that Rhes deletion in the mouse striatum caused remarkable aggregation of mutant HTT (mHTT) and neurodegeneration during the presymptomatic stage (22 weeks old) of HD KI mice.However, Rhes deletion during the symptomatic stage (36 weeks old) of HD KI mice did not exacerbate neuropathology. Furthermore, we observed increased P62, decreased LC3-II and beclin-1 levels without mTOR activation following Rhes deletion, indicating reduced autophagy activity in a mTOR-independent manner. These results suggest that Rhes plays a protective role during the presymptomatic stage of HD KI mice.